EFEKTIVITAS SWEDISH MASSAGE TERHADAP KUALITAS TIDUR DAN TINGKAT INSOMNIA LANSIA - Rianayanti Asmira Rasam; Ressa Andriyani Utami (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2020)
Background. Insomnia is a complaint that often occurs in the elderly, if not resolved it can reduce the quality of life of the elderly. Proper handling can improve the quality of life of the elderly. The Aim of The Study. This study aims to determine the effectiveness of Swedish massage on sleep quality and the level of insomnia in the elderly. Subjects and Methods. The research design used quasi experiment non equivalent control group pretest-post test. The number of samples in this study were 62 people who were taken randomly, divided into an intervention group of 37 peoples who were given swedish massage therapy for 7 days and a control group of 25 peoples who were given worship therapy 2x a week, before and after the intervention vital signs were measured. Research analysis using binary logistic and t test difference. Results. The results of binary logistic analysis and multiple linear regression showed a significant effect between swedish massage therapy on sleep quality on day 7 and the level of insomnia (p value